Modulation of Septo-Hippocampal Neural Responses in Anesthetized and Behaving Rats by Septal AMPA Receptor Mechanisms - Ibrahim, Khairunisa Mohamad; Ariffin, Mohammed Zacky; Khanna, Sanjay (Frontiers in Neural Circuits, 2021)
This study explored the effects of septal glutamatergic transmission on septal-hippocampal theta activity via intraseptal microinjection antagonist at AMPA receptors (AMPAR) and NMDA receptors (NMDAR). The current results showed that AMPAR antagonist, NBQX (2,3-dihydroxy-6-nitro-7-sulfamoyl-benzo[f]quinoxaline-2,3-dione, 20g/l, 0.5l), evoked differential effects in anesthetized and behaving male rats. In anesthetized rats, NBQX microinjection attenuated both hippocampal theta field power and frequency evoked by reticular stimulation and by direct activation of medial septum (MS) via microinjection of carbachol, a cholinergic agonist. However, the effect of NBQX on reticular stimulation- and intraseptal carbachol-evoked suppression of CA1 population spike was relatively weak. In behaving rats, NBQX microinjection mainly led to a significant decrease in hippocampal theta frequency during exploration in an open field and during the initial phase of nociception in the formalin test. However, NBQX neither affected hippocampal theta power nor ambulation in both tests. In contrast, intraseptal NMDAR antagonist, AP5 (2R-amino-5-phosphonovaleric acid, 5g/l, 0.5l) attenuated hippocampal theta power during open field test and induced a dramatic increase in ambulation in both open field and formalin tests. Although an amperometric analysis showed a sustained increase in extracellular glutamate levels in the MS following formalin hind paw injection, the current findings showed that NBQX but not AP5 was antinociceptive. These findings suggest a dichotomy of MS glutamate receptors’ role where NMDAR has a greater influence on acute sensorimotor behaviors and hippocampal theta power while AMPAR modulates acute sensory behaviors and hippocampal theta generation